APLIKASI MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN WEDDING PHOTOGRAPHY “SERENITY PHOTOWORKS” - Alhuda, Afif; Dharta, Firdaus Yuni; Lubis, Flori Mardiani (Peneliti.net, 2024)
This research aims to understand the communication process undertaken by Serenity Photoworks in marketing their products through the Instagram platform, as well as the supporting and inhibiting factors in product marketing and the effectiveness of using Instagram as a media tool. The research methodology used in this study is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results of the study show that Serenity Photoworks has effectively utilized Instagram as a communication and marketing platform for its products. They are active in creating content and utilizing various Instagram features such as Instastory, Instagram Feed, and Instagram Reels. The supporting and inhibiting factors are based on Product, Price, Promotion, and Place. The communication effectiveness of Serenity Photoworks on Instagram has successfully served as a medium for promoting their photography products with visually appealing and high-quality content. The utilization of Instagram as an effective platform to attract potential customers, particularly among millennials, is a key factor in the marketing strategy of Serenity Photoworks.